Distortions to Agricultural Incentives in Light of Trade Policy : A Study on Pakistan - Ejaz, Neelam; Ahmad, Maha (World Bank, Washington, DC, 2019)
Agriculture forms the backbone of Pakistan’s economy. Despite the fact that the share of agriculture in the GDP has declined over the years, the sector continues to play an important role in the socio-economic structure of the country. About 60 percent of the population lives in rural areas of Pakistan, the majority of which is dependent on agricultural activities for their livelihood. Yield growth for most crops and livestock products in Pakistan has stagnated and become more variable in recent years. Furthermore, sizable gaps persist between achievable and realized productivity in most crops, and diversification and a move to higher value-added agricultural commodities has been limited, predominantly in the crops sector.